Direct anterior approach total hip arthroplasty requires less supplemental acetabular screw fixation and fewer blood transfusions than posterior approach. Issue 4 (July 2017) - Colacchio, Nicholas D.; Cleary, Mark X.; Reid, Daniel; Trofa, David; Pevear, Mary E.; Smith, Eric L.
Abstract : Background: This study evaluates the use of supplemental acetabular cup screw fixation during direct anterior approach (DAA) versus posterior approach total hip arthroplasty (THA). Methods: A retrospective review of all THAs performed by a single fellowship-trained total joint surgeon at a tertiary academic medical center between January 2010 and January 2013 identified 136 primary THAs (124 patients). The following variables were analyzed: age, body mass index (BMI), American Society of Anesthesiologists (ASA) score, operative side, surgical approach, operative time, estimated blood loss, blood transfusion, implant design, number of acetabular screws used, offset (high, standard, or coxa vara), cup anteversion, and cup abduction. Results: There were 31 DAA and 105 posterior-approach primary THAs performed. Significantly fewer acetabular screws were used in DAA compared to posterior approach (1.0 vs. 1.9 screws, P <0.001). Patients who received acetabular screws had a significantly increased likelihood of requiring a blood transfusion (OR=4.4). Patients who received blood transfusions had significantly more acetabular screws placed than patients who did not receive transfusions (2 vs. 1.2 screws, P <0.001). DAA patients had a significantly lower mean BMI than posterior approach patients (26.2 vs. 30.6). There were no significant differences in age, gender, operative time, cup abduction, cup anteversion, estimated blood loss, or blood transfusions between the two cohorts. Conclusions: The number of supplemental acetabular screws used in THA performed by DAA was significantly less than during a posterior surgical approach, and supplemental screw fixation was associated with a significantly increased likelihood of requiring a blood transfusion. Surgeons should consider these factors when deciding which THA approach may be best for an individual patient.